A novel chattering-free pi sliding mode control for a class of nonlinear underactuated systems. (29th August 2019) - Liu, Shuang; Li, Pengwei
For the tracking and stabilisation control problem of nonlinear underactuated systems, a novel chattering-free sliding mode control approach is proposed in this paper. According to Lyapunov theorem of stability, sliding mode can be around the sliding surface in a finite time by the control law. Moreover, the chattering phenomenon caused by the discontinuous control law can be eliminated by the proposed approach. Simulation results for a bipedal walking robot system demonstrate the feasibility and efficiency of the introduced design. Furthermore, it is noteworthy that the developed approach can be widely applied to kinds of underactuated nonlinear control problems.